ADSORPTION OF TOXIC METALS ONTO ECO-FRIENDLY AND COST-EFFECTIVE SHEA (Vitellaria paradoxa ) NUT SHELL BIOCHAR IN AQUEOUS PHASE - Quainoo, A. K.; Duwiejuah, A. B.; Cobbina, S. J. (UDS International Journal of Development, 2019)
The present study was to evaluate adsorption of cadmium (Cd), mercury (Hg) and lead (Pb) in mono and multi- metal component systems onto shea nut shell biochar. The adsorption capacity of Cd in mono aqueous phase with contaminant limits of 0.04 mg/l, 0.08 mg/l and 0.20 mg/l onto shea nut shell biochar produced under pyrolysis temperatures of 350 ± 5 °C and 700 ± 5 °C (SB350 and SB700) were 1 mg/g, 2 mg/g and 5 mg/g, respectively. The correlation coefficient values for Langmuir and Freundlich isotherms ranged from 0.28 to 0.99 for mono system and 0.49 to 0.96 for binary and ternary systems by SB350 and SB700. The binary mixtures showed Hg interactions with Cd and Pb ions onto SB350 are antagonistic in nature whilst mercury interaction with ions in ternary systems was synergistic in nature. The study revealed no clear cut difference between adsorption patterns of the mono, binary and ternary metals systems. The study showed complete adsorption of ions in single and competitive systems by shea nut shell boichar that is attributable to the biochar having strong affinity for ions. The mono, binary and ternary adsorption systems are very important in the estimation of toxic metal adsorption efficiencies onto biochar, in accordance with how they are released into receiving waters. For accurate estimation of Cd, Pb and Hg adsorption capacity of shea nut shell biochar, there is the need to conduct further multi-metal adsorption studies in the natural environments. Keywords: Adsorption, Aqueous Phase, Toxic Metals, Shea Nut Shell Biochar